Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Prestasi Administrasi Transaksi SIswa Kelas XI BDP1 Semester Ganjil SMK Negeri 1 Tabanan Tahun Pelajaran 2022/2022 - Sulaiman, Sulaiman (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
This study aims to improve transaction administration learning achievement with the problem based learning learning model for class XI BDP1 students in odd semester of SMK Negeri 1 Tabanan for the 2022/2023 academic year. As for the research subjects, students who have a low understanding of basic competence analyze the procedure for recording proof of transactions in transaction administration subject which is characterized by low understanding, activity, enthusiasm, and students' courage in expressing their ideas. Actions are designed in two cycles. At the end of the action of each cycle, monitoring and evaluation are carried out, which are then reflected in the results of the evaluation for planning the next cycle. Monitoring was carried out using observation techniques, interviews and student understanding tests. Based on the evaluation results, it can be seen that in cycle I there was an increase in students' mastery of basic competence in analyzing the procedure for recording transaction evidence in the subject of transaction administration with the learning achievement score increasing from the average initial learning achievement score of 69.11 increasing to 75.33 with the percentage increase was 9.69%. Meanwhile, after being given action in cycle II there was an increase in the average value of student achievement increasing from 75.33 to 83.06 with an increase percentage of 10.88%. So that the average percentage of increasing the level of mastery of basic competencies in analyzing the procedure for recording evidence of transactions in transaction administration subjects between cycle I and after cycle II is 20.57%. (9.69% plus 10.88%)